Pengembangan Sistem Surat Digital Berbasis Laravel untuk Meningkatkan Efisiensi Administrasi dan Pelayanan Publik - Romadoni, Jiki; Haji Ahmad Makie; Beny Rahman Hakim; Buti Styawan; Siti Raudah (Journal of Informatics Management and Information Technology, 2025)
Kaladan Village in Candi Laras Utara District, Tapin Regency, faces challenges in providing administrative services for cover letters due to the use of manual processes based on Microsoft Office and paper filing. This causes risks of data loss and delays in the approval process by the village head. The proposed solution is the digitalization of public services through the development of a web-based information system. This system is designed to address administrative needs, including approval of cover letters, data management, report generation, application submissions, and tracking of application statuses with digital signatures. The research findings indicate that this system improves service efficiency by up to 40%, reduces data loss risks, and speeds up administrative processes. With the implementation of this system, services are expected to become more efficient, accurate, and accessible to the community while serving as a model for other villages in improving public services.